(untitled) (Journal of Social Sciences Review, 2023)
Res judicata is a matter of public policy and right during any litigation. The doctrine is discussed in the Code of Civil Procedure 1908 (CPC 1908) with an exhaustive instance of applicability and inapplicability in Section 11. However, the explanation given in Section 11 appears in-exhaustive considering the broader spectrum of cases and scenarios. This manuscript consolidates the instances that complement section 11 to formulate the ever-exhaustive list of instances for the proper application of res judicata. The study conducted case-based research and extracted the rules formulated in the judicial decisions by the higher judiciary. The present research contemplates a better comprehension of the rules that can save the public right of litigation and also inhibit unnecessary instances of frivolous litigation.